ANTECEDENTS OF DESTINATION IMAGE IN NATURAL PROTECTED AREA: THE MODERATING ROLE OF PERCEIVED VALUE - Chin, Ying-Sin; Mohamad, Abang Azlan; Lo, May-Chiun; Wan Ibrahim, Wan Hashim; Ha, Shiaw-Tong (Editura Universitati din Oradea, 2020)
Ecotourism is a nature-oriented tourism idea that is flourishing and with promising outlook. The present study attempts to explore the importance of local communities’ attitude, carrying capacity and destination attractiveness & resources towards destination image by adopting perceived value as a moderator on examining the antecedents on destination image. Data were collected from 146 tourists who have visited Bako National Park, Sarawak. The research employs WarpPLS 6.0 and the results revealed that local communities’ attitude, carrying capacity and destination attractiveness & resources have impact on destination image. Perceived value has moderating effect between destination attractiveness & resources and destination image.